EDUCATION, DISCIPLINE WITHOUT BORDERS? EDUCATION, DISCIPLINE WITHOUT BORDERS? - GARCÉS, Luis Javier (Utopía y Praxis Latinoamericana, 2021)
Someone could point out that Education is not a discipline but an object of study, and that the discipline to which this object corresponds is Pedagogy, considered as “the” science of Education. However, I will allow myself to incidentally cast doubt on these claims because of the inconclusive epistemological discussion about "the" sciences of education; by the relativity that I assign to certain modern taxonomic schemes; due to their Eurocentric nature; because I am interested in debating the complexity of the problem as transdisciplinary, multidisciplinary and interdisciplinary; by the framework of the power dispute in which the proposed discussion is inserted.